2006
DOI: 10.1002/joc.1272
|View full text |Cite
|
Sign up to set email alerts
|

Climatic change and interannual fluctuations in the long-term record of monthly precipitation for Seoul

Abstract: We examine the characteristic climatic changes recorded in the long-term precipitation data for Seoul, Korea. Since precipitation data for Seoul has been accumulated for over 230 years, it is very useful in studying climatic changes in the monsoon region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
1
23
0
Order By: Relevance
“…Since areaaveraged precipitation was used, the variances in precipitation were smaller than those at the synoptic station of Seoul. However, as shown in Ha and Ha (2006), the variance in the annual standard deviations representing the annual structure is larger than that in the annual means for all four periods, indicating the importance of the annual structure in year-to-year variability. The anomalous components of annual structure are largest during the period 1931-1960.…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 80%
See 2 more Smart Citations
“…Since areaaveraged precipitation was used, the variances in precipitation were smaller than those at the synoptic station of Seoul. However, as shown in Ha and Ha (2006), the variance in the annual standard deviations representing the annual structure is larger than that in the annual means for all four periods, indicating the importance of the annual structure in year-to-year variability. The anomalous components of annual structure are largest during the period 1931-1960.…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 80%
“…The CRI significantly correlates with the indices in terms of SLP, 500 hPa geopotential height, 200 and 850 hPa wind (Ha et al, 2005). Ha and Ha (2006) reported that, compared to the annual mean, the annual structure of the EASM has greater influence on interannual variability and climate change. The total variance in the rainfall over Korea from 1901 to 2002 was investigated and the variance in the annual means and that in the annual standard deviations for the total period compared for the three separate periods ( Table 1).…”
Section: Interannual and Interdecadal Variabilitymentioning
confidence: 93%
See 1 more Smart Citation
“…Several studies have used this station data set to represent the Korean rainfall and to study its variability. For example, using KMAR, Cha et al [2007] revealed that long‐term changes and extreme events in rainfall occurred in summer during the period of 1954–2004, and Ha and Ha [2006] examined climatic changes using the long‐term rainfall data for Seoul. Kripalani et al [2002] investigated the statistical relationship between winter‐to‐spring snow depth over Russia and summer rainfall over South Korea using KMAR.…”
Section: Data and Analysis Methodsmentioning
confidence: 99%
“…The varying time of temporal series is a place where from then on, another statistical distribution prevails over the data (Ha and Ha, 2006). The point of confluence of the two diagrams of u and u 0 indicates a substantial point of variation and the existence of the trend.…”
Section: Trend Detectionmentioning
confidence: 99%